Circadian expression of the presynaptic active zone protein bruchpilot in the lamina of Drosophila melanogaster. Issue 1 (20th July 2012) - Górska‐Andrzejak, Jolanta; Makuch, Renata; Stefan, Joanna; Görlich, Alicja; Semik, Danuta; Pyza, Elzbieta
Abstract In the fly's visual system, the morphology of cells and the number of synapses change during the day. In the present study we show that in the first optic neuropil (lamina) of Drosophila melanogaster, a presynaptic active zone protein Bruchpilot (BRP) exhibits a circadian rhythm in abundance. In day/night (or light/dark, LD) conditions the level of BRP increases two times, in the morning and in the evening. The same pattern of changes in the BRP level was detected in whole brain homogenates, thus indicating that the majority of synapses in the brain peaks twice during the day. However, these two peaks in BRP abundance, measured as the fluorescence intensity of immunolabeling, seem to be regulated differently. The peak in the morning is predominantly regulated by light and involves the transduction pathway in the retina photoreceptors. This peak is present neither in wild‐type Canton‐S flies in constant darkness (DD), nor in norpA7 phototransduction mutant in LD. However, it also depends on the clock gene per, because it is abolished in the per0 arrhythmic mutant. In turn, the peak of BRP in the evening is endogenously regulated by an input from the pacemaker located in the brain. This peak is present in Canton‐S flies in DD, as well as in the norpA7 mutant in LD, but is absent in per01, tim, 01 and cry01 mutants in LD. In addition both peaks seem to depend on clock gene‐expressing photoreceptors and glial cells of the visual system. © 2012 Wiley Periodicals, Inc. Develop Neurobiol, 2013